Solve the equation for a. k = 4a + 9ab a = k(4 + 9b) a = 4(k + 9b) a = a =

Solve the equation for a. K = 4a + 9ab

a = K(4 + 9b)
a = 4(K + 9b)
a = a equals StartFraction 4 plus 9 b Over K EndFraction equals h.
a = a equals StartFraction K Over 4 plus 9 b EndFraction equals h.


a = k/(4 + 9b)

Step-by-step explanation:

Here, we want to make a the formula subject

We have this as;

k = a(4 + 9b)

a = k/(4 + 9b)

Allen is a Technology guy, He basically works on Top articles related to Technology, Gadgets, and more. To know more about his work.
Leave a comment